PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN (STUDI KASUS PADA HOTEL GRAND SUKA PEKANBARU) - Gea, Risihati; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The research was conducted at the Grand Suka Hotel Pekanbaru, located at Jalan SoekarnoHatta kav.148 Pekanbaru, Riau. The purpose of this study was to determine the effect of Service Quality And Pricing On Costumer Satisfaction (a case study at Hotel Grand Suka Pekanbaru) partially and simultaneously. In this research, the method used is quantitative descriptive analysis with the SPPS program. The population in this study were all consumers who purchased rooms at the Grand Suka Hotel Pekanbaru in the last year, namely 2019, as many as 100 people. The sample in this research is all consumers of Hotel Grand Suka Pekanbaru as many as 100 respondents. To determine the sample using the census method. The technique of collecting data through questionnaires and interviews, the types and sources of data using primary data and secondary data, the technique of collecting measurements using a liker scale.From the analysis of data which includes validity test, reliability, simple linear regression analysis, multiple linear analysis, determination analysis and significance test with t test (partial test), and f test (simultaneous).  Keywords: Service Quality; Pricing; Customer satisfaction